A new test to detect monotonic and non-monotonic types of heteroscedasticity - Celik, Resit (TAYLOR & FRANCIS LTD, 2017)
A direct parametric test is proposed to detect monotonic and non-monotonic types of heteroscedasticity. After giving brief information about non-monotonic types of heteroscedasticity, the test algorithm is introduced. Proposed test and usual heteroscedasticity tests are compared on monotonic and non-monotonic types of heteroscedasticity in real and artificial data.
Keywords: Monotonic heteroscedasticity; non-monotonic heteroscedasticity; heteroscedasticity tests; absolute transformed centered external variable; Mathematics